Perbedaan Kebersihan Sepertiga Apikal Saluran Akar dari Smear Layer Menggunakan Sistem Aktivasi Ultrasonik dan Sonik - Della Puspita; Rudy Djuanda; Angela Evelyna (Maranatha Christian University, 2019)
Irrigant activation is important for successful endodontic treatment. There are some of activation technique those are manual irrigation with needle irrigation and mechanics irrigation with sonic, and ultrasonic activation. The aim of this study was to compare the effectiveness between sonic and ultrasonic activation technique as irrigation activation for smear layer removal in apical third of the root canal. Fifteen mandibular premolars were used. NaOCl 2,5% and EDTA 17% was used as an irrigant. Sample were divided into 3 equal group (n=5) according to the final activation technique: group I as a needle irrigation II as a ultrasonic activation, group III sonic activation. Root canals were split longitudinnaly and subjected to scanning electron microscope with 2000x magnification. Data were evaluated using statistics kruskall wallis and mann whitney. The result of this study shows there were statistically significant differences in staistics Mann Whitney on group III were more clean than group II p < 0,05. Sonic technique more effective in removal of smear layer in apical third of the root canal than ultrasonic activation technicque. Important to noted the variant of irrigant and activation.